2015
DOI: 10.1155/2015/438749
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis in Central Morocco: Seasonal Fluctuations of Phlebotomine Sand Fly in Aichoun Locality, from Sefrou Province

Abstract: Cutaneous leishmaniases (CL) are endemic in Morocco. They are common in the human population in different localities such as Aichoun in Sefrou province, Morocco. This study was carried out in Aichoun locality from April to October 2012 in order to study the spatiotemporal trends of the main Leishmania phlebotomine vectors in this focus. Overall, 1171 sand flies, belonging to four species, were collected by sticky traps. Phlebotomus sergenti was the predominant species (78.4%) followed by Ph. perniciosus (10.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
5
20
1
Order By: Relevance
“…The work of El Miri et al [33] in SidiKasem, in the west of Province Moulay Yaâcoub has found a sex ratio of 4 males to one female, which is very close to our results. However, the work of Talbi et al [38] on the province of Sefrou in the south of our study area, found that males are 7.54 times more abundant than females. For all species sex ratio is >1, however, for the Lahouiti et al…”
Section: Sex Ratiocontrasting
confidence: 66%
“…The work of El Miri et al [33] in SidiKasem, in the west of Province Moulay Yaâcoub has found a sex ratio of 4 males to one female, which is very close to our results. However, the work of Talbi et al [38] on the province of Sefrou in the south of our study area, found that males are 7.54 times more abundant than females. For all species sex ratio is >1, however, for the Lahouiti et al…”
Section: Sex Ratiocontrasting
confidence: 66%
“…Our study area belongs to the semiarid located at an altitude between 220 and 2,000 m. Indeed, Rioux et al in 1984 showed that the distribution of various vector species of leishmaniasis is mainly linked to the climate [41]. At the level of the study area, the result could be explained by the type of climate prevailing in this region, the semiarid microclimate and the mountainous areas in which Phlebotomus sergenti was the most commonly collected sandfly species in the same area followed by Phlebotomus perniciosus and Phlebotomus longicuspis [38]. Ph.…”
Section: Spatial Distribution Of Leishmaniasismentioning
confidence: 87%
“…In addition, our observations are in line with the typical aspect of the transmission of this type of leishmaniasis (CL), whose infestation phase dates back to the summer-autumn period of the past year, which is closely related to the dynamics of the vector Phlebotomine, Ph. sergenti [38][39][40].…”
Section: Monthly Distribution Of Leishmaniasis Casesmentioning
confidence: 99%
See 2 more Smart Citations